Editorial - Thematic Dossier: Reenactment studies in the performing arts (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
Information about the content of the Thematic Dossier: Reenactment studies in the performing arts.
Keywords: editorial; articles; special feature